Changes in proteases and chemical compounds in the exterior and interior of sufu, a Chinese fermented soybean food, during manufacture. (January 2018) - Liu, Jingjing; Han, Beizhong; Deng, Shuhan; Sun, Shiping; Chen, Jingyu
Abstract: Sufu is a pleasant-tasting, traditional Chinese fermented soybean food that is rich in nutrients. The manufacture of sufu includes four steps: preparation of tofu, preparation of pehtze, salting of pehtze and ripening of salted pehtze in a dressing mixture. Based on electrophoresis and 1 H-NMR methods, the changes in protease and chemical compounds in the exterior and interior of sufu were investigated during fermentation. The results indicated that proteases with various molecular masses (162.6, 124.6, 104.3, 66.9, and 44.9 kDa) existed in both the exterior and interior of pehtze, salted pehtze, and ripened sufu, which proved that proteolytic reactions in the exterior and interior of sufu were occurring simultaneously. Furthermore, ethanol, ethylene glycol, glucose, isopropanol, and mannitol were the major carbonic compounds present in sufu, and amino acids were the predominant nitrogen compounds present in sufu. Correlation analysis revealed important links between protease activity and chemical compounds, e.g., succinate, histamine, and trimethylamine, were significantly positively correlated with protease activity in sufu. Through these results, the effect of protease on chemical compounds in sufu was identified, which can be useful for the improvement of enzymatically ripened sufu. Highlights: The changes in proteases and chemical compounds in the exterior and interior of sufu were investigated during fermentation. Proteolytic reactions in the surface and core of sufu were occurring simultaneously. Correlation analysis revealed important links between protease activity and chemical compounds in sufu samples.